New synonyms and lectotypes in Aspicilia (Megasporaceae, Ascomycota) - Nordin, Anders (Phytotaxa, 2015)
The genus Aspicilia A.Massal. s.l. (Megasporaceae Pertusariales Ascomycota) has a worldwide distribution and the species are common components in the lichen vegetation on exposed rocks in a wide variety of biomes from hot deserts to Arctic tundras. The genus has a reputation of being taxonomically extremely complicated, which is partly caused by the extreme morphological variation and phenotypic plasticity of the species (Nordin 2013; Nordin et al. 2007, 2008, 2010; Owe-Larsson et al. 2008, 2011; Roux et al. 2011). The only existing taxonomic treatment of the genus with a wide scope was published by Magnusson (1939), who applied very narrow species circumscriptions in most cases. Here a number of new synonyms are presented and discussed, most of which are names introduced by Magnusson (loc. cit.), and lectotypes of Lecanora griseopallida and Sagedia laevata are designated.